2011
DOI: 10.1182/blood-2010-05-285973
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein receptor II regulates pulmonary artery endothelial cell barrier function

Abstract: Mutations in bone morphogenetic protein receptor II (BMPR-II) underlie most heritable cases of pulmonary arterial hypertension (PAH). However, less than half the individuals who harbor mutations develop the disease. Interestingly, heterozygous null BMPR-II mice fail to develop PAH unless an additional inflammatory insult is applied, suggesting that BMPR-II plays a fundamental role in dampening inflammatory signals in the pulmonary vasculature. Using static-and flow-based in vitro systems, we demonstrate that B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
107
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(118 citation statements)
references
References 38 publications
6
107
4
1
Order By: Relevance
“…28 These findings are contradicted by studies addressing the role of bone morphogenetic protein receptor type 2 (BMPR2) mutations in familial pulmonary arterial hypertension, where silencing of BMPR2 in human endothelial cells increases permeability, 36 and mice transfected with mutated BMPR2 exhibit substantial vascular leak in vivo. 37 Herein, we demonstrated a TRPC4-dependent increase in the permeability of isolated lungs from PAH Fischer rats after store depletion with thapsigargin.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…28 These findings are contradicted by studies addressing the role of bone morphogenetic protein receptor type 2 (BMPR2) mutations in familial pulmonary arterial hypertension, where silencing of BMPR2 in human endothelial cells increases permeability, 36 and mice transfected with mutated BMPR2 exhibit substantial vascular leak in vivo. 37 Herein, we demonstrated a TRPC4-dependent increase in the permeability of isolated lungs from PAH Fischer rats after store depletion with thapsigargin.…”
Section: Discussioncontrasting
confidence: 40%
“…Furthermore, BMPR2 silencing and Sugen models of PAH exhibit interaction with respect to permeability, indicating that vascular endothelial growth factor receptor and BMPR pathways are linked in regulating endothelial barrier function. 36 We suggest that increased vascular permeability may be a distinguishing feature of a subset of PAH patients, and therefore warrants further study.…”
Section: Discussionmentioning
confidence: 99%
“…Heterozygous Bmpr2 mutant mice have pulmonary endothelial cell (PEC) dysfunction with decreased endothelium-dependent relaxation in isolated intrapulmonary pulmonary artery preparations (8). In addition, mice with conditional deletion of Bmpr2 in the endothelium develop spontaneous pulmonary hypertension and have endothelial barrier dysfunction associated with increased pulmonary vascular leak and perivascular inflammation (11)(12)(13). Increased perivascular inflammation also occurs in patients with pulmonary hypertension (14 -16).…”
Section: Pulmonary Arterial Hypertension (Pah)mentioning
confidence: 99%
“…Reduced BMPR2 expression and function is also described in patients with IPAH or with APAH who do not have a mutation (8). Loss of BMPR2 impairs PAEC survival (2)(3)(4)(5) and barrier function (11). Our previous studies demonstrated that BMPR2 signaling activates b-catenin/peroxisome proliferator-activated receptor (PPAR) g-mediated transcription of PAEC genes, such as apelin (3,4).…”
mentioning
confidence: 99%